Clinical Reasoning: A 52-year-old woman with progressive proximal weakness - Enduri, Sailaja (Lippincott Williams & Wilkins, 2014)
A 52-year-old woman presented with a 12-year history of progressive limb weakness. She first had trouble climbing stairs and later difficulty getting up from a chair. She also experienced hip and shoulder pain. Over the previous 2 years, combing her hair became difficult. She denied any eyelid drooping, double vision, chewing or swallowing difficulty, slurred speech, shortness of breath, numbness, tingling, autonomic symptoms, or cognitive problems. She did not have any rashes or joint pain. She had no other medical problems and was not taking any medications. She was born full-term and had normal developmental milestones. She was able to keep up with her peers and was a good runner during her childhood. The patient was of German descent and her father and paternal uncle developed leg weakness in their early 40s and were diagnosed with limb-girdle muscular dystrophy (LGMD). They died in a plane crash in their late 40s. The patient's older brother and her uncle's son developed leg weakness in their early 40s and were also diagnosed with LGMD. Both died in their mid-to-late 50s due to respiratory failure. Her brother also had peripheral neuropathy. The diagnosis of LGMD in all family members is based on clinical presentations and muscle biopsies. Genetic studies were not performed. There was no family history of dementia, bone disorder, or motor neuron disease. Her neurologic examination revealed symmetrical weakness of shoulder and hip girdle muscles (Medical Research Council [MRC] grade 4), as well as anterior leg compartment muscles (MRC grade 4+). She also had scapular winging bilaterally. There was no myotonia, muscle rippling, fasciculation, muscle atrophy, or hypertrophy. Deep tendon reflexes were normal except for absent ankle reflexes on both sides. Cognition, cranial nerves, sensory examination, and coordination were normal. She had high-arched feet and hammertoes. There was neither joint contracture nor spinal rigidity.